Nicholas of Cusa’s Dialogue with Augustine: The Measure of the Soul’s Greatness in De Ludo Globi - Powrie, Sarah (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
Nicholas of Cusa’s De Ludo Globi (1463) explores the tensions between the soul’s terrestrial and transcendent aspirations; between its desire to engage materiality through creative self-expression and to remove itself from its historically-bound identity in mystical contemplation. Many of Cusa’s arguments about the soul in this work are indebted to Augustine’s De Quantitate Animae (388), and while the cardinal emphasizes different capacities of the soul, many of his analogies originate from this Augustinian source. Clearly Cusa’s most significant appropriation is the dialogical framework itself, which being situated at the threshold between discursive reason and mystical contemplation becomes an effective vehicle for exploring the soul’s cognitive and spiritual aptitudes. While both dialogues illustrate the rational or creative capacities of the embodied soul, they ultimately acknowledge the limitations of these capacities, and of the dialogic form itself, when compared to the higher reaches of the soul’s contemplative powers.